Kedudukan Kepala Desa dalam Peningkatan Kesejahteraan Masyarakat di Desa Toabo Kecamatan Papalang Kabupaten Mamuju - Juwita Pratiwi (Departemen Ilmu Pemerintahan Fisip Unhas, 2019)
This research aims to find out how the position of village chief to increase welfare community in the village of Toabo, with looked the role of village chief as the authority implement task from the local government district/city and as the authority implement based on origin and local scale village in increase the welfare community. The type of this research used is deskriptif analysis that give a systematic social overview, factual and accurate about obtained in the field. Data collection used the techniques of observation, interview, and the study of literature. The result of the research indicate that the position of village chief to increase welfare community in Toabo village as the authority implement task from the local government of district/city less than optimal because the health fasilities and infrastructure and environment have not done well white, the role of village chief as the authority implement based on rights origin and local scale village on health and nutrition, employment, houses and environment, still limitation the provision of fasilities, infrastructure and job.